Malleable Mental Accounting: The Effect of Flexibility on the Justification of Attractive Spending and Consumption Decisions - Cheema, Amar; Soman, Dilip (Journal of Consumer Psychology, 2006)
Mental accounts are often characterized as self‐control devices that consumers employ to prevent excess spending and consumption. However, under certain conditions of ambiguity, the mental accounting process is malleable; that is, consumers have flexibility in assigning expenses to different mental accounts. We demonstrate how consumers flexibly classify expenses, or construct accounts, to justify spending. An expense that can be assigned to more than one account (i.e., an ambiguous expense) is more likely to be incurred than an unambiguous expense that is constrained either by existing budgets or by previously constructed accounts. We explore the justification processes that underlie these results and their implications for mental accounts as self‐control devices.